Mobilizing support and negotiating change: women's organizations building constituencies in Bangladesh - Nazneen, Sohela; Sultan, Maheen (BRAC University, 2013)
This paper describes and analyzes how three national level women’s organizations in Bangladesh mobilized support around a particular issue among their membership and allies. The paper uses social movement/resource mobilization theories and feminist studies on the state and social movement for grounding this research. The focus is on the decade of the 1990s and the present decade. Through these case studies the research aims to capture the diversity of the strategies used by these organizations for building constituencies‐‐internally and externally, i.e., within the civil society organizations, media, political parties and state bureaucracies. All three case study organizations, have strategically packaged the issues differently for their own members and external supporters depending on the emotional response they want to invoke and the social costs involved in packaging an issue in a specific way. The strategies these organizations used to build support within the state, political parties and the civil society are influenced by the following factors: i) the contradictory positions of the Bangladeshi state on gender equity issues; ii) aid dependence and politicization of the civil bureaucracy. These factors have led feminist organizations to engage with the state in a strategic manner i.e. seizing opportunities, as and when they arise, to further their cause. This type of behavior is motivated by the need to preserve autonomy, organizational legitimacy, and on the use of personal connections to access state machinery. Generally, women’s organizations have tried to distance themselves from the political parties and have not directly lobbied for their issues to be incorporated into the agendas. This is due to the fact that the costs of engaging with political parties remain high and these organizations have not established themselves as major players in the political system. The nature of exchange with the civil society is marked by considerations for mutual reciprocity based on personal obligations, legitimacy concerns, and asymmetrical power relations, which at times have adversely affected accountability relations within coalitions.